DOI: 10.31274/rtd-180813-10231
|View full text |Cite
|
Sign up to set email alerts
|

Self-perceived youth leadership life skills development among Iowa 4-H members

Abstract: Determine the predictors of leadership life skills development from among participation in 4-H leadership activities, achievement expectancy, years in 4-H, age, gender, place of residence, academic achievement, and selected organizational and family variables. The Iowa State University Human Subjects Review Committee reviewed this project and concluded that the rights and welfare of the human subjects were adequately protected; that potential benefits and expected values of the knowledge sought outweighed risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…Anderson, Bruce, Jones, and Flowers (2015) reported YLLSD scores of livestock exhibitors at the North Carolina State Fair were high, and the high scores are an indicator that livestock project exhibition may facilitate YLLSD. Similarly, Walker (2006) and Morris (1996) stated youth perceived livestock exhibition to cultivate YLLSD. Boleman, Cummings, and Brier's (2004) found parents perceived their child's life skills were being enhanced by 4-H beef project participation.…”
Section: Agricultural Youth Programming Yllsd and Livestock Skillatmentioning
confidence: 99%
“…Anderson, Bruce, Jones, and Flowers (2015) reported YLLSD scores of livestock exhibitors at the North Carolina State Fair were high, and the high scores are an indicator that livestock project exhibition may facilitate YLLSD. Similarly, Walker (2006) and Morris (1996) stated youth perceived livestock exhibition to cultivate YLLSD. Boleman, Cummings, and Brier's (2004) found parents perceived their child's life skills were being enhanced by 4-H beef project participation.…”
Section: Agricultural Youth Programming Yllsd and Livestock Skillatmentioning
confidence: 99%
“…A student participant stated, "I like classes that are taught through our everyday life experiences, so that I can actually practice instead of just listening to the teachers to repeat the textbook." Considering the fact, which has been discussed in Chapter 2, that confluent education theory, requires the employment of experiential learning and that the learning of practical skills occurs when experiential learning is employed (Morris, 1996), the researcher concluded that students would enjoy learning practical skills together with technical skills.…”
Section: Enabler Focus Group Findings and Discussionmentioning
confidence: 99%
“…This focus requires the employment of experiential learning practice to implement the educational program. Morris (1996) The traditional exam-oriented education system in rural China deprives even elementary school students the opportunities of experiential learning. Under such educational practices, not only are the mind and the body of the learners separated, but also the learners and the rest of the society are separated.…”
Section: Significance Of This Studymentioning
confidence: 99%
See 2 more Smart Citations